AVALIAÇÃO DE PROCESSOS DE ADSORÇÃO DE METAIS PESADOS: UM ESTUDO EXPERIMENTAL COM PROPOSTAS DE UTILIZAÇÃO DE SUBPRODUTOS - Silva, Francky Roger Araujo da (2005)
For several years rivers, basins and channels are receiving direct and indirectly residues containing heavy metals. It was verified that those present metals in the sediments and in the particles in suspension are absorbed easily for the human beings, through physiologic processes or of nutrition. Due to the several problems caused by the heavy metals, it was studied the interaction process among different heavy metals for different minerals and a way of this use as catalyst of chemical reactions for obtaining iodoidrins. Iodoidrins are composed organic of great usefulness in epoxy synthesis and in medicine. For such, solutions of the metals chrome, cadmium and lead were used; and two different minerals: montmorilonite and kaolin. The procedure utilized were: mineralogical analyses, chemistry, granulometric studies, density measuring, adsorption with metals, zeta potential measures, statistical analysis of the results, optimization of adsorption and organic reactions. It could be observed that the montmorilonite presented better acting of adsorption, due to presence of more silicate adsorved more easily in this structure. It was also observed that metals of larger valence are adsorption with larger easiness and that the pH values affect more significantly than the time. As for the results of the organic reactions, it was verified that the formation of the iodoidrin became viable after addition of heavy metals, because the same ones form a compound with the iodine, allowing the processing of the reaction. It can be concluded that there is possibility for removal heavy metals using clays and use in chemical reactions, increasing this efficiency and collaborating with the medical research.